2016
DOI: 10.22495/cbv12i3art7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the government procurement fraud: The independent auditor’s point of view.

Abstract: The objective of this study was examining the factors affecting the government procurement fraud. Based on the fraud triangle and the theory of planned behavior, this study proposed seven hypothesis, those are tested by regression analysis. This study used primary data gathered by surveys to members of The Boards of the Republic Indonesia- Financial Auditors, who act as external auditors for the Government. They were asked to assess factors influencing the government procurement of goods and services fraud. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A study by Said et al (2017) found that pressure does not influence employee fraud occurrence in the banking industry in Malaysia. In addition, Zulaikha et al (2016) discovered that financial pressure has no positive correlation with fraud conduct. Her reasoning for this conclusion is that financial incentives for procurement committees are highly regulated in Indonesia, making it difficult for the committee to commit fraud.…”
Section: Research Frameworkmentioning
confidence: 99%
“…A study by Said et al (2017) found that pressure does not influence employee fraud occurrence in the banking industry in Malaysia. In addition, Zulaikha et al (2016) discovered that financial pressure has no positive correlation with fraud conduct. Her reasoning for this conclusion is that financial incentives for procurement committees are highly regulated in Indonesia, making it difficult for the committee to commit fraud.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Scholars and managers have also considered a number of other possible explanations for fraud; such as competitive economic environments, the organizational culture, and personal morals. Among these ethical belief factors stand out as most significant (Bezuidenhoud, 2014;Burnett, 2017;Manurung, Suhartadi, & Saefudin, 2015;Zulaikha & Hadiprajitno, 2016;Weber, Kurke, & Pentico, 2003). What regulates individuals' choices of appropriate behaviours, beliefs and thought towards others is what is regarded as ethics.…”
Section: Introductionmentioning
confidence: 99%